Substrate use of Pseudovibrio sp. growing in ultra-oligotrophic seawater. - Anne Schwedt; Michael Seidel; Thorsten Dittmar; Meinhard Simon; Vladimir Bondarev; Stefano Romano; Gaute Lavik; Heide N Schulz-Vogt (PLoS ONE, 2015)
Marine planktonic bacteria often live in habitats with extremely low concentrations of dissolved organic matter (DOM). To study the use of trace amounts of DOM by the facultatively oligotrophic Pseudovibrio sp. FO-BEG1, we investigated the composition of artificial and natural seawater before and after growth. We determined the concentrations of dissolved organic carbon (DOC), total dissolved nitrogen (TDN), free and hydrolysable amino acids, and the molecular composition of DOM by electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI FT-ICR-MS). The DOC concentration of the artificial seawater we used for cultivation was 4.4 μmol C L(-1), which was eight times lower compared to the natural oligotrophic seawater we used for parallel experiments (36 μmol C L(-1)). During the three-week duration of the experiment, cell numbers increased from 40 cells mL(-1) to 2x10(4) cells mL(-1) in artificial and to 3x10(5) cells mL(-1) in natural seawater. No nitrogen fixation and minor CO2 fixation (< 1% of cellular carbon) was observed. Our data show that in both media, amino acids were not the main substrate for growth. Instead, FT-ICR-MS analysis revealed usage of a variety of different dissolved organic molecules, belonging to a wide range of chemical compound groups, also containing nitrogen. The present study shows that marine heterotrophic bacteria are able to proliferate with even lower DOC concentrations than available in natural ultra-oligotrophic seawater, using unexpected organic compounds to fuel their energy, carbon and nitrogen requirements.